2024
DOI: 10.1111/ijd.17186
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cardiovascular disorders in hidradenitis suppurativa patients: a large‐scale, propensity‐matched global retrospective cohort study

Piotr K Krajewski,
Łukasz Matusiak,
Sascha Ständer
et al.

Abstract: BackgroundPatients with hidradenitis suppurativa (HS) often suffer from comorbid diabetes, metabolic syndrome, and hyperlipidemia and, therefore, are susceptible to the development of cardiovascular diseases (CVDs). Moreover, systemic inflammation plays a vital role in the development of atherosclerosis. The creation of atherosclerotic plaque is characterized by endothelial dysfunction driven by elevated concentrations of interleukin (IL)‐1, IL‐6, and IL‐18 among others, as well as tumor necrosis factor (TNF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Prior observational research has looked into the connection between HS and CVDs. 29 , 30 , 31 , 32 , 33 For instance, Reddy et al. 34 found that, compared with non‐HS patients, those with HS had a 21% increased risk of MI after adjusting for relevant cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Prior observational research has looked into the connection between HS and CVDs. 29 , 30 , 31 , 32 , 33 For instance, Reddy et al. 34 found that, compared with non‐HS patients, those with HS had a 21% increased risk of MI after adjusting for relevant cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Krajewski et al 4 explored the association between HS and increased cardiovascular risk in a large-scale, propensitymatched global retrospective cohort study. This study involving 144,100 HS patients and 144,100 healthy controls identified HS as an independent risk factor for various cardiovascular diseases, highlighting the systemic nature of the condition and its potential to affect organs beyond the skin.…”
Section: Integrated Care For Hidradenitis Suppurativamentioning
confidence: 99%